Comparison of Ultrasound Guided Bilateral Subcostal Transversus Abdominis Plane Block versus Local Infiltration of Port Site with Bupivacaine in Patients Undergoing Laparoscopic Cholecystectomy under General Anesthesia - Paudel, Bandana; Paudel, Sumitra; Rai, Pramod; Dahal, Sagar; Pokhrel, Anuja (Birat Journal of Health Sciences, 2021)
Introduction: Patients undergoing laparoscopic cholecystectomy have moderate post-operative pain in the early post-operative period. There are several modalities to manage pain in the postoperative period. Subcostal transversus abdominis plane block is one of the effective methods for pain management. The objective of our study was to compare the analgesic efficacy of subcostal transversus abdominis block versus local infiltration at the port site with bupivacaine in patients undergoing Laparoscopic cholecystectomy under general anesthesia.Methodology: This is a prospective randomized study of 60 patients of age group 18 – 60 years of either gender, of ASA PS I and II scheduled for laparoscopic cholecystectomy under general anesthesia and were randomly divided into two groups. At the end of the surgery 20ml of 0.25% bupivacaine was administered with ultrasound guided subcostal transversus abdominis plane block bilaterally in group T and local infiltration at the port sites in group L. Visual analogue scale at 0, 2, 6, 12 and 24 hours at rest, time of rescue analgesia and opioids consumption were recorded.Results: Both the groups were comparable with each other to assess pain scores and analgesic requirements. Group T had less pain at rest (